Science, Politics, and the Two Cultures Issue: A Contribution to the External History of the Origin of the Sociology of Scientific Knowledge - Benda, Libor (Teorie vědy / Theory of Science, 2014)
The study deals with the so far unexplored external history of the origin of the sociology of scientific knowledge. Its aim is to analyse the external factors which contributed to the emergence of this discipline, for the purpose of explaining why it emerged right in the 1970s at the Science Studies Unit at the University of Edinburgh and in the very form of the so-called strong programme in the sociology of knowledge. Through the Unit's founder C. H. Waddington the study focuses on two episodes: the emergence of the politically engaged movement of British left-wing scientists in the 1930s pushing forward the concept of a social function of science, and the politicisation of the so-called two cultures issue in the post-war Great Britain that lead to changes in British scientific policy and educational system. In its concluding part the study then turns attention to the individual interests of those members of the Unit who were directly behind the development of the strong programme.